2D‐localization and delocalization effects in quantum Hall regime in HgTe wide quantum wells. Issue 7 (16th March 2016) - Gudina, Svetlana V.; Arapov, Yurii G.; Neverov, Vladimir N.; Podgornykh, Sergey M.; Popov, Mikhail R.; Shelushinina, Nina G.; Yakunin, Mikhail V.; Dvoretsky, Sergey A.; Mikhailov, Nikolay N.
Abstract: We have measured the longitudinal and Hall resistivities in the quantum Hall regime at magnetic fields B up to 9 T and temperatures T = (2.9–50) K for HgTe/HgCdTe heterostructure with wide HgTe quantum well. The results are analysed within the scaling concept for the conductivity on the delocalized states at the center of the Landau level and within the variable‐range hopping model for the conductivity on the localized states between the Landau levels. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)